ARAHAN PENGELOLAAN BLOK PEMANFAATAN KESATUAN PENGELOLAAN HUTAN LINDUNG (KPHL) UNIT VI PADA AREAL MODEL MIKRO DAS (MDM) TALAWAAN - Badrun ,. Zaini; Bobby Vian Jhon Polii; Hengki Djemie Walangitan (Sam Ratulangi University, 2019)
This study aims to: (1) Analyze management models with Geographic Information Systems (GIS), (2) Arrange alternative directions for priority management with a combination of GIS and Analytical HirarchyProcess (AHP) and policy direction of land tenure in forest areas that are in the utilization block KPHL Unit VI which is in Talawaan MDM. The method used in this study is a survey method, namely: a method forobtaining field data by means of systematic observation, measurement and recording of the object under study and supported by the results of laboratory analysis. Sampling and field measurements are carried out using strata techniques with consideration to adjusting the location of the collection. Analysis of the data used: a) Estimating the amount of erosion using the formula Universal Soil Loss Equation (USLE), b) The combination of Geographic Information Systems and Analytical Hierarchy Process (AHP) is used to prepare alternatives for decision making. The results of this study indicated that the Management Model formed in the study area is the Community Forest Management Model (HKm) and Community Plantation Forest (HTR) and with a management period of 35 years and can be extended thereafter. Furthermore, the direction of management priorities according to AHP analysis with economic, ecological and social targets is to implement a management model with Land Utilities Type (LUT) Agrorestry, enrichment LUT and reforestation LUT with an economic target value of 429 points, ecological target value of 143 points and weight social target value of 429 points. The direction of the Government's policy for the completion of land tenure in this forest area is to provide management access to forest areas in the form of Social Forestry Program with the Community Forest Management Model (HKm) and Community Plantation Forest (HTR).*eprm*